Pelatihan membuat media Komik, Scratchbook, dan Mading untuk Menumbuhkan Minat Baca Anak di Rumah Literasi Sidomulyo Kulon Progo - Ignatia Esti Sumarah; Khoirun Nisa; Aditya Dwi Prananda; Putri Handayani; Rizal Fadly Ardiansyah; Viraesti Damayati; Valent Milenio Boas Santosa (Lembaga Pengembangan Kinerja Dosen, 2024)
Literacy is an individual's ability to understand, use and analyze information through various forms of language. Literacy includes understanding reading, writing and arithmetic, as well as the ability to process information critically and creatively. Through training in making media, comics and sketchbooks. Training activities are carried out in three stages, namely preparation, implementation and evaluation. Where training activities were carried out twice at the Sidomulyo Kulon Progo Literacy House. This training activity supports increasing children's interest in literacy at the Literacy House. Apart from that, the activities and making of wall media, comics and scratchbook can increase children's creativity.